Unmanned aerial vehicle based coverage enhancement in wireless adhoc network - et al., Mohd Asim Sayeed (International Journal of Advanced Science and Technology, 2020)
The Unmanned Aerial Vehicle(UAV) assisted adhoc network formations suffer from imbalanced network coverage. Ground to air collaborative network need to be optimized for efficient resource utilization. However the random deployment of ground adhoc network makes it a challenge to suitably place the UAV network to enhance the network capacity. A multi-UAV collaborative environment is susceptible to coverage problems, which leads towards minimized coverage, service overlap and non-optimal UAV path. In this paper, differential evolution based optimized coverage solution is proposed. The model presents a technique for placement of aerial nodes in ways that enhances the network resource utilization, provides coverage to ground nodes and minimizes the overlapping coverage in multi-UAV deployment. The model takes into account both service and coverage overlaps, aiming to maximize the number of nodes served by setting up optimized UAV movement coordinates. In computer simulations the proposed model yields substantial increase in throughput and reduces delay in packet delivery.